Twisted-Wonderland : the manga. Book of Octavinelle. 1 - Toboso, Yana, 1984-; Hazuki, Wakana (VIZ Media, 2025)
Stranded in the world of Twisted Wonderland, Yu must brave a magical school filled with ghosts, monsters, and uncooperative students! Whisked away to the world of Twisted Wonderland and enrolled in the magical school known as Night Raven College, Yu encounters a strange scenario-his fellow students are doing too well on their exams! But there couldn't be anything sinister behind great test scores, could there?